Interpolation by Bivariate Polynomials Based on Multivariate F-Truncated Powers (Communications in Mathematical Research, 2021)
The solvability of the interpolation by bivariate polynomials based onmultivariate F-truncated powers is considered in this short note. It unifies the pointwise Lagrange interpolation by bivariate polynomials and the interpolation by bivariate polynomials based on linear integrals over segments in some sense.